Respostas

2013-06-07T00:06:08-03:00

se temos:

x=\frac{1}{7}\ e\ y=\frac{1}{100} so é substituir as equaçoes:

vamos fazer a primeira e ver o resultado:

 

x^2-2xy\\(\frac{1}{7})^2-2*\frac{1}{7}*\frac{1}{100}\\\frac{1}{49}-\frac{2}{700} mmc de 49 e 700= 4900

\frac{100-14}{4900}=\frac{86}{4900}=\\\\\frac{43}{2450}

 

agora a outra:

 

\frac{1}{7}+\frac{1}{100}  mmc de 7,100= 700

\frac{100+7}{700}=\frac{107}{100}

  • Usuário do Brainly
2013-06-07T00:23:23-03:00

Temos que:

 

\text{x}^2-2\text{x}\cdot\text{y}

 

Se \text{x}=\dfrac{1}{7} e \text{y}=\dfrac{1}{100}, temos:

 

\left(\dfrac{1}{7})\right)^2-2\cdot\dfrac{1}{7}\cdot\dfrac{1}{100}=\dfrac{1}{49}-\dfrac{2}{700}=\dfrac{100-14}{4~900}=\dfrac{86}{4~900}

 

Analogamente, temos:

 

\text{x}+\text{y}=\dfrac{1}{7}+\dfrac{1}{100}=\dfrac{100+7}{700}=\dfrac{107}{700}